PENGARUH KONSENTRASI RAGI ROTI TERHADAP KUALITAS VIRGIN COCONUT OIL (VCO) SEBAGAI RANCANG BANGUN LEMBAR KERJA SISWA (LKPD) BAHAN BIOTEKNOLOGI KONVENSIONAL SMA - Tri Beti Indri; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to determine the effect of the concentration of baker's yeast on the quality of Virgin Coconut Oil (VCO) and the design of the Student Worksheet (LKPD) for biotechnology material for class XII SMA in May-October 2021. This research was carried out in 2 stages, namely the experimental stage: the effect of concentration baker's yeast on the quality of Virgin Coconut Oil (VCO) and the LKPD design stage: analysis of the potential development of biotechnology teaching materials for class XII SMA. The study used an experimental method by conducting experiments at the Biology Laboratory, Faculty of Teacher Training and Education (FKIP) and the Chemistry Laboratory, Faculty of Fisheries and Marine Sciences (Faperika), Pekanbaru. Sampling was carried out using a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The parameters in this study were yield, water content, free fatty acids and organoleptic. Based on the results of the analysis of variance (Anava) with an accuracy level of 0.05 or 5%, the concentration of baker's yeast showed a significant effect on the quality of Virgin Coconut Oil (VCO). Giving baker's yeast with a concentration of 20% gave the best quality improvement of Virgin Coconut Oil and based on the analysis of potential research results, it can be used as a student worksheet design for biotechnology material for class XII SMA.Key Words: Virgin Coconut Oil (VCO), fermentation, baker's yeast, LKPD Design